The importance of corporate social responsibility for responsible consumption: Exploring moral motivations of consumers. (16th October 2018) - Golob, Urša; Podnar, Klement; Koklič, Mateja Kos; Zabkar, Vesna
Abstract: The motivations and actions of socially responsible consumers are important for the success of corporate social responsibility (CSR). The issues of responsible consumption or consumer social responsibility (CnSR) nevertheless continues to receive insufficient research attention. To remedy this shortcoming, we built on the value‐belief‐norm theory (VBN) and propose that normative factors induce consumers to enact CnSR in their buying behaviour. Using a survey of 462 consumers, we examined the relationships between values (self‐transcendent and self‐enhancement), an individual's view on the importance of CSR, awareness of negative societal consequences, ascribed responsibility for prosocial behaviour, personal norms, social norms, and CnSR. The findings indicate that CnSR can indeed be comprehensively explained with the variables included in VBN. Moreover, social norms also tend to significantly shape CnSR. The theoretical and practical implications of our results are discussed.